LAND DISPUTE SETTLEMENT REVIEW FROM MINANGKABAU TRADITIONAL LAW (CASE STUDY OF LIMAPULUH REGENCY, WEST SUMATRA PROVINCE CITY) - Muhammad Nasir (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this research is: (1) To understand the process of clearing estate lawsuit based on the customs of Minangkabau. (2) To understand the obstacles found during the case of clearing estate lawsuit based on the customs of Minangkabau. This research, utilizes empirist method in where law is socially, culturally, and das sein because in this research, the primary datas are collected from real cases. This research proves that; (1) The clearing process of heirloom lawsuit in Minangkabau is accomplished by the system of “Ladder up” and “Stairs down” starting from the neighborhood of clan, the neighborhood of tribe, and the neighborhood of Nagari. If the clearing process were not to reach an agreement, the clearing process shall be continued to the neighborhood of Nagari. (2) The obstacles that I find in the clearing process of heirloom lawsuit can be observed from two points of view. First, from the perspective of cultural leaders is the lack of willingness, the lack of economical resources, and the letter of bequest. Second, from the perspective of prosecutors is the element of time, the lack of agreement that can be mutually reached, and differences of opinion. Based on the data of my research, it is recommended that; (1) in order to avoid the obstacles mentioned by the researcher, the side of the prosecutors should require a person that can act as mediator (not a cultural leader) in order to prevent an event in which the tribal leaders from both side might clash. (2) For the government of West Sumatra to consider making local regulation regarding the inheritance of an estate with cultural value and allow the local regulation be spread in order to avoid further compication regarding estate lawsuit.